International law and transitional governance : critical perspectives - De Groof, Emmanuel, 1983-; Wiebusch, Micha, 1987- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This volume examines the role of international law in shaping and regulating transitional contexts, including the institutions, policies and procedures that have been developed to steer constitutional regime changes in countries affected by catalytic events. The book offers a new perspective on the phenomenon of conflict-related transitions, whereby societies are re-constitutionalized through a set of interim governance arrangements subject to variable degrees of internationalization. Specifically, this volume interrogates the relevance, contribution and perils of international law for this increasingly widespread phenomenon of inserting an auxiliary phase between two ages of constitutional government. It develops a more nuanced understanding of the various international legal discourses surrounding conflict- and political crisis-related transitional governance by studying the contextual factors that influence the transitional arrangements themselves, with a specific focus on international aspects, including norms, actors and related forms of expertise. In doing so, the book builds an important bridge between comparative constitutional law and international legal scholarship in the practical and highly dynamic terrain of transitional governance. This book will be of much interest to practitioners and students of international law, diplomacy, mediation, security studies and International Relations"--
Introduction / Emmanuel De Groof and Micha Wiebusch -- The Features of Transitional Governance / Emmanuel De Groof and Micha Wiebusch -- Contextualizing Conflict-Related Transitional Governance Since 1989 / Adam Day and David M. Malone -- Constituting Transitions: Predicting Unpredictability / Christine Bell and Robert A. Forster -- No Strings Attached? : Constraints on External Advice in Internationalized Constitution-Making / Sumit Bisarya -- The gap between international legitimacy and legality of transitional regimes / Noam Wiener -- Legitimising transitional authorities through the international law of self-determination / Matthew Saul -- The End(s) of Transition / Zinaida Miller -- The Ambitions and Traumas of Transitional Governance : Expelling Colonialism, Replicating Colonialism / Vasuki Nesiah -- The Future(s) of Transitional Governance and International Law / Emmanuel De Groof and Micha Wiebusch
Includes bibliographical references and index.
Keywords: Interim governments; State succession; Recognition (International law); Interim governments; Recognition (International law); State succession; Transitional Justice